Application Effect Analysis of the Mie Scattering Theory Based on Big Data Analysis Technology in the Optical Scattering Direction. (20th September 2022) - Chen, Suting
Abstract : In order to study the characteristics of wake, an application method of the Mie scattering theory based on big data analysis technology in the optical scattering direction is proposed in this paper. Firstly, based on the scattering theory, the optical scattering model of a single bubble is simulated on the computer. It is concluded that the light scattering properties of a single bubble are closely related to the bubble diameter and relative refractive index. Based on the single bubble scattering model, the properties of bubble group scattering are further discussed. Under the condition of irrelevant scattering, the scattering of the bubble group satisfies the linear superposition of single bubble scattering. Under the assumed mathematical model of bubble group scattering, the scattered light intensity of wake can be measured experimentally, and then, the velocity, diameter, and density distribution of the bubble group can be calculated by using the mathematical inversion algorithm. The experimental results show that the diameter of the main bubbles in the bubble group is about 240, accounting for about 50% of the whole bubble group in number, the bubbles with a diameter of about 140 account for 24% of the whole bubble group, and the bubbles with a diameter of about 350 account for 24% of the whole bubble group. Conclusion . It is feasible to detect the wake by the backscattered light of the wake.